MELD score is predictive of 90-day mortality after veno-arterial extracorporeal membrane oxygenation support. Issue 4 (April 2022) - Karnib, Mohamad; Haraf, Rebecca; Tashtish, Nour; Zanath, Erica; Elshazly, Tarek; Garcia, Raul Angel; Billings, Scott; Fetros, Michael; Bradigan, Allison; Zacharias, Michael; Abu-Omar, Yasir; Elgudin, Yakov; et al.
Background: The Model for End-Stage Liver Disease (MELD) score was originally described as a marker of survival in chronic liver disease. More recently, MELD and its derivatives, MELD excluding INR (MELD-XI) and MELD with sodium (MELD-Na), have been applied more broadly as outcome predictors in heart transplant, left ventricular assist device placement, heart failure, and cardiogenic shock, with additional promising data to support the use of these scores for prediction of survival in those undergoing veno-arterial extracorporeal membrane oxygenation (VA ECMO). Methods: This study assessed the prognostic impact of MELD in patients with cardiogenic shock undergoing VA ECMO via a single-center retrospective review from January 2014 to March 2020. MELD, MELD-XI, and MELD-Na scores were calculated using laboratory values collected within 48 h of VA ECMO initiation. Multivariate Cox regression analyses determined the association between MELD scores and the primary outcome of 90-day mortality. Receiver operating characteristics (ROC) were used to estimate the discriminatory power for MELD in comparison with previously validated SAVE score. Results: Of the 194 patients, median MELD was 20.1 (13.7–26.2), and 90-day mortality was 62.1%. There was a significant association between MELD score and mortality up to 90 days (hazard ratio (HR) = 1.945, 95% confidence interval (95% CI) = 1.244–3.041, p = 0.004) after adjustment for age, indication for VA ECMO, and sex. The prognostic significance of MELD score for 90-day mortality revealed an AUC of 0.645 (95% CI = 0.565–0.725, p < 0.001). MELD-Na score and MELD-XI score were not associated with mortality. Conclusion: MELD score accurately predicts long-term mortality and may be utilized as a valuable decision-making tool in patients undergoing VA ECMO.